EFEKTIVITAS PELAKSANAAN PENGABDIAN MASYARAKAT DI KABUPATEN PESISIR SELATAN - Nasution, Syamsarina; Mu’arrif, Zul Ihsan; Harahap, Samsul Bahry; Bustami, Bustami (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Community Service Program (KKN) conducted by students of the State Islamic Institute (IAIN) Kerinci in South Pesisir Regency, West Sumatra, aims to apply academic knowledge in addressing various social, economic, and educational challenges faced by the local community. Through collaboration between the university, local government, and the community, this program is designed to provide benefits and improve the quality of life for the community. Evaluations from various parties, including Field Supervising Lecturers (DPL), Village Heads, students, and the community, indicate a high level of satisfaction with the effectiveness of this program. DPLs highlight the program's success in providing a strong structure and apparatus support, contributing to capacity building for the community and students. Village Heads appreciate the integration and strong support from local leaders, while students show valuable learning experiences that support their growth. Evaluations from the community indicate the KKN program's direct positive impact on their welfare. The results of the evaluations affirm that the KKN program in South Pesisir Regency has successfully achieved its community service objectives, reflecting the successful implementation of participatory collaboration between the university, local government, and the community in inclusive and sustainable development. This program highlights the importance of community service as an integral part of higher education's tri dharma and demonstrates the added value of a collaborative approach in solving community problems.